IDENTIFYING AND DESCRIBING TRANSLATION PROBLEMS: A LONGITUDINAL CASE-STUDY IN TRANSLATOR TRAINING - Gregorio Cano, Ana (2017)
This research is framed within the area of translation and interpreting studies and more specifically within the field of translation didactics. The general research objective of this study is to observe and analyze the repercussions of Translation undergraduate courses at five different universities in Spain. With empirical methods combining quantitative and qualitative analysis relying on a macro-study of more than 1,000 subjects and a longitudinal study of 37 students, the research focuses specifically on the development of the strategic competence (SC) and, particularly, the student’s capacity to identify and describe translation problems. Furthermore, in the case of the longitudinal study, four hypotheses were tested against the students’ answers. In this paper, we present the results of hypothesis number 4: whether the richness of the metalanguage used by the TI students evolves from the beginning to the end of their study program. The longitudinal study results do not show any patterns for the development of the SC, although the metalanguage used by students does evolve.